Applying Principles of Management Innovation in Advertising Agencies - Andrea Rubik (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
With the advertising industry and practice changing significantly in the last decade, it is likely that the existing management practices in advertising agencies also need some transformation. Through exploring management innovation principles and practices, novel practices might be applied by advertising agencies to exploit changes in their environment and enhance organizational performance. This paper explores the application and framework for novel management practices in an advertising agency. A proposed model is based on the principles of management innovation and the activities needed to drive management innovation. The topic is relevant for advertising agencies to understand better management innovation possibilities and enhancement it could create for them to compete in new markets and stay ahead of new competition.
Keywords: O31; L22; 330; management innovation; advertising agency; management